Serum Acetylcholinestrase (Ache) Activity At Different Stages Of Gestation In Triple Cross Cattle - Padodara, R. J.; Arya , J. S. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Serum Acetylcholinestrase (AChE) activity (mmol/ml/hr) was studied in triple cross pregnant heifers (20) and cows (24) at days 90, 150, 210 and 275 of gestation. AChE activity significantly (P<0.01) doubled at day 150 at day 90 in both heifers and cows. The activity further decreased significantly (P<0.01) on day 210 and day 275 of gestation in both heifers and cows. The values at day 275 in heifers and cows were found to be at par with the values on day 90 of gestation.